2004
DOI: 10.1095/biolreprod.104.032573
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Mechanisms and Modulation of Activin A- and Transforming Growth Factor β-Mediated Differentiation in Cultured Hen Granulosa Cells1

Abstract: Undifferentiated granulosa cells from prehierarchal (6- to 8-mm-diameter) hen follicles express very low to undetectable levels of LH receptor (LH-R) mRNA, P450 cholesterol side chain cleavage (P450scc) enzyme activity, and steroidogenic acute regulatory (StAR) protein, and produce negligible progesterone, in vitro, following an acute (3-h) challenge with either FSH or LH. It has previously been established that culturing such cells with FSH for 18-20 h induces LH-R, P450scc, and StAR expression, which enables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 41 publications
5
33
0
Order By: Relevance
“…Our results show that treatment of cultured secondary follicles with activin-A does increase the follicular level of FSH-R mRNA, which is in accordance with the previously demonstrated activin-induced FSH-R formation in rat granulosa cells (XIAO et al, 1992). When combined with FSH, activin-A similarly also stimulates expression of FSH-R mRNA in granulosa cells from 6-8 mm hen follicles (JOHNSON et al, 2004). These studies suggest that effects of activin-A on the synthesis of FSH-R appear simultaneous with its role in the amelioration of the sensitivity of follicular cells to this gonadotropin.…”
Section: Discussionsupporting
confidence: 92%
“…Our results show that treatment of cultured secondary follicles with activin-A does increase the follicular level of FSH-R mRNA, which is in accordance with the previously demonstrated activin-induced FSH-R formation in rat granulosa cells (XIAO et al, 1992). When combined with FSH, activin-A similarly also stimulates expression of FSH-R mRNA in granulosa cells from 6-8 mm hen follicles (JOHNSON et al, 2004). These studies suggest that effects of activin-A on the synthesis of FSH-R appear simultaneous with its role in the amelioration of the sensitivity of follicular cells to this gonadotropin.…”
Section: Discussionsupporting
confidence: 92%
“…As it has been shown that ActA increased LH-R mRNA expression in 6-8 mmGC (Johnson et al 2004), the present and previous data lead us to propose that GC of prehierarchical follicles approaching selection, which are primarily FSH-driven, have reduced expression of key ActRs (ActRI and ActRIIB) and therefore a diminished responsiveness to Act. In turn, as follicles are selected and become more responsive to LH, ActRI and ActRIIB mRNA expression is upregulated leading to greater co-stimulation by Act.…”
Section: Discussionsupporting
confidence: 64%
“…ActA also enhanced FSH-R and LH-R mRNA expression in GC from preovulatory follicles (Johnson et al 2006). An ActA-induced increase in FSH-R mRNA expression has also been observed in GC from preheirarchical hen follicles (Johnson et al 2004, 2006, Woods & Johnson 2005.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations